2006
DOI: 10.1136/thx.2005.057745
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnoea in men with type 2 diabetes

Abstract: Background: A study was undertaken to establish the prevalence of obstructive sleep apnoea (OSA) in men with type 2 diabetes. Methods: Men with type 2 diabetes from local hospital and selected primary care practitioner databases received questionnaires about snoring, apnoeas, and daytime sleepiness based on the Berlin questionnaire. Selected respondents had overnight oximetry to establish whether they had OSA. Comparisons of oximetry were made with those from a previous general population study. HbA1c results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
236
3
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(263 citation statements)
references
References 28 publications
10
236
3
14
Order By: Relevance
“…38 People with diabetes are at higher risk of coronary artery disease and congestive heart failure, which may contribute to the development of atrial fibrillation. Finally, after accounting for obesity, people with diabetes have higher prevalence of obstructive sleep apnea, 39 which may lead to atrial fibrillation. 40 Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…38 People with diabetes are at higher risk of coronary artery disease and congestive heart failure, which may contribute to the development of atrial fibrillation. Finally, after accounting for obesity, people with diabetes have higher prevalence of obstructive sleep apnea, 39 which may lead to atrial fibrillation. 40 Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is very common in patients with type 2 diabetes (T2D) (6)(7)(8)(9)(10). We previously reported that OSA is associated with peripheral neuropathy, nephropathy, and estimated glomerular filtration rate decline in patients with T2D independently of obesity (10,11).…”
mentioning
confidence: 99%
“…27 Patients with mild reduction in arterial hemoglobin saturation due to sleep apnoea have more severe retinopathy than those whose airways do no obstruct at night. Positive pressure ventilation in such patients also reduces the rate of progression of DR. [28][29][30][31][32] Does illuminating the retina reduce the risk of progression of retinopathy?…”
Section: Evidence That Oxygen Supplementation Improves Visual Functiomentioning
confidence: 99%